Kepemimpinan inovatif kepala madrasah dalam mengembangkan program unggulan di mi salafiyah banaran kabupaten kediri - Jamil, Dina Rahmatun Najma (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the forms and strategies of innovative leadership practiced by the head of the madrasah in developing flagship programs at MI Salafiyah Banaran, Kediri Regency. In the context of modern education, school leaders are required to be visionary and innovative in order to respond to societal changes and improve institutional competitiveness. The head of MI Salafiyah, Mr. Misbakul Munir, S.Pd., demonstrates innovative leadership through vision-based planning, collaboration with teachers and stakeholders, learning innovation, strengthening of religious culture, and external partnerships. These strategies have successfully produced several flagship programs such as Tahfidzul Qur’an, Kajian Kitab Kuning, Salafiyah English Club, Inclusive Class, and Islamic Science Inspirational Class.This research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings show that innovative leadership plays a crucial role in improving academic quality, strengthening students’ religious character, and enhancing achievements. The impact includes increased teacher motivation, community trust, and students’ achievements at regional and national levels. This study concludes that innovative leadership is a key factor in developing an excellent, adaptive, and competitive madrasah in the era of globalization.